A case of Type 2 appendiceal diverticulum perforated and a review of the literature. (2020) - Fiordaliso, Michele; De Marco, Antonia Flavia; Costantini, Raffaele
Highlights: Acute appendicitis and appendiceal diverticulosis can present with pain in the right lower quadrant, which makes differential diagnosis difficult. Preoperative imaging tests do not contribute to the definitive diagnosis because the diagnosis is mainly determined by the histological study. The perforation rate of appendicitis diverticulitis is four times higher than the perforation rate of acute appendicitis. In addition, there may be a risk of developing peritoneal pseudomyxoma in some patients with appendiceal diverticulosis. Laparoscopic appendectomy is considered a safe and appropriate treatment for simple appendiceal diverticulitis. Abstract: Background: Appendiceal diverticulosis disease is a rare entity. An perforated appendiceal diverticulosis mimicking acute appendicitis is a extremely unusual surgical finding and the reported prevalence is between 0.014 and 3.7%. Case report: We report the case of an elderly man, who presented with a typical clinical image of acute appendicitis and underwent laparoscopic surgery. Intraoperative an acute appendicitis with localized peritonitis was identified and a laparoscopic appendectomy was performed, but pathologic analysis demonstrated a type 2 appendiceal diverticulitis. Conclusion: Appendiceal diverticulosis disease should be included in differential diagnosis of patients presenting with clinical signs of an acute appendicitis and prompt surgical treatment is essential in order to avoid severe complications.